2021
DOI: 10.3390/app11031345
|View full text |Cite
|
Sign up to set email alerts
|

Index of Body Inflammation for Maxillofacial Surgery Purpose-to Make the Soluble Urokinase-Type Plasminogen Activator Receptor Serum Level Independent on Patient Age

Abstract: Background: The serum suPAR level is affected in humans by it increases with age. Therefore it makes difficult interpretation and any comparison of age varied groups. The aim of this study is to find simple way to age independent presentation of suPAR serum level for maxillofacial surgery purpose. Methods: In generally healthy patients from 15 to 59 y.o. suPAR level was tested in serum before orthognathic or minor traumatologic procedures. Five ways to make the suPAR serum level assessment independent of age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Similar findings were obtained by Yang et al, who reported that mean leucocyte and lymphocyte counts in the children group were both significantly higher than in adults [ 13 ]. Several recent studies have highlighted changes in the bacterial load of maxillofacial infections with age [ 31 , 33 , 34 ]. A relatively higher percentage of the younger patients had negative bacterial culture results in comparison to those in the senior group [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were obtained by Yang et al, who reported that mean leucocyte and lymphocyte counts in the children group were both significantly higher than in adults [ 13 ]. Several recent studies have highlighted changes in the bacterial load of maxillofacial infections with age [ 31 , 33 , 34 ]. A relatively higher percentage of the younger patients had negative bacterial culture results in comparison to those in the senior group [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Novel markers of immune activation and inflammation (suPARs) raise hopes of accurately assessing the impact of activation of local inflammatory foci. In immunologically compromised patients [45,46], e.g., prior to bone marrow transplantation, aggressive systemic treatment in leukemia, or radiochemotherapy of the head and neck region, the detection of activating dentate inflammatory foci in lymphoma would be invaluable.…”
Section: Discussionmentioning
confidence: 99%
“…For the suPAR analysis, the samples were thawed, thoroughly mixed and centrifuged, and their suPAR concentrations were assessed. Next, Index of Body Inflammation (IBI) was calculated according to the equation below, to present the suPAR results in age-independent way [8]:…”
Section: Methodsmentioning
confidence: 99%